(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Chemistry is a very visual subject. As professional chemists we take for granted the ability to understand detailed figures and graphs. In the laboratory, we rely on our eyesight for even the simplest procedures such as weighing out reagents and monitoring reactions. We also use specialist instruments that require precise alignment and operation.